2006
DOI: 10.1111/j.1460-9568.2006.04638.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine efflux in the rat striatum evoked by electrical stimulation of the subthalamic nucleus: potential mechanism of action in Parkinson's disease

Abstract: The precise mechanism whereby continuous high-frequency electrical stimulation of the subthalamic nucleus ameliorates motor symptoms of Parkinson's disease is unknown. We examined the effects of high-frequency stimulation of regions dorsal to and within the subthalamic nucleus on dopamine efflux in the striatum of urethane-anaesthetized rats using constant potential amperometry. Complementary extracellular electrophysiological studies determined the activity of subthalamic nucleus neurons in response to simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 62 publications
7
106
1
1
Order By: Relevance
“…The loss of excitatory input of the STN under DBS may thus lower the basal level of dopaminergic neuron activity in these structures and ultimately alter their reactivity to food and cocaine reward. It is interesting to note however that some studies suggest that STN DBS may result in increased activity of the DA system (35). The dissociation of STN effects, when low workload and high workload were required, such as in the FR1 and PR schedule of reinforcement, has been previously observed after manipulation of the DA system.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of excitatory input of the STN under DBS may thus lower the basal level of dopaminergic neuron activity in these structures and ultimately alter their reactivity to food and cocaine reward. It is interesting to note however that some studies suggest that STN DBS may result in increased activity of the DA system (35). The dissociation of STN effects, when low workload and high workload were required, such as in the FR1 and PR schedule of reinforcement, has been previously observed after manipulation of the DA system.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 High-frequency stimulation of the STN may directly activate nigrostriatal and pallidonigral fiber tracts and thus contribute to a therapeutic effect by modulating the release of dopamine. [62][63][64][65][66] Although animal studies have shown a significant increase in striatal dopamine with STN HFS and have offered an attractive explanation for improvement of PD symptoms coincident with a reduction in antiparkinsonian medication, to date there is no evidence that a similar process occurs in humans. Several PET studies using [ 11 C]raclopride to measure dopamine binding have failed to show changes during STN HFS, suggesting that the therapeutic effects of STN stimulation are not mediated by striatal dopamine release.…”
Section: Activation Of Fiber Tracts Of Passagementioning
confidence: 99%
“…This hypothesis has been raised on the basis of the observation that similarly to lesions to the OFC, lesions to the subthalamic nucleus increase compulsive lever-pressing and decrease dopamine and serotonin (but not glutamate and GABA) in the striatum (Winter et al, 2008a). It is also noteworthy that pharmacological inactivation and high-frequency stimulation of the subthalamic nucleus, that exert an anticompulsive effect in the signal attenuation model (Klavir et al, 2009), have been reported to increase dopamine levels in the striatum (Bruet et al, 2001;Meissner et al, 2001;Lee et al, 2006). To the best of our knowledge there are no studies that assessed the effects of these manipulations on striatal serotonin.…”
Section: Ofc Lesionmentioning
confidence: 99%